Austrian delegates to the Paris Congress (1900) of the 2nd International. From: Beilage zur Festschrift "Zum 1. Mai 1890" - Baelz, Jh.,
Austrian delegates to the Paris Congress (1900) of the 2nd International. From: Beilage zur Festschrift "Zum 1. Mai 1890".